KEAMPUHAN AYAT AL-QUR’AN SEBAGAI SARANA PENGUSIR SETAN (ANALISIS BUKU SENJATA SPRITUAL SANTRI) - Muhammad Shulhi Alhadi Siregar (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2018)
This paper attempts to examine how the process of transmitting and transforming the Qur'an in the book